The Effect of Mobile Marketing Design on Consumer Mobile Shopping. (14th April 2021) - He, Junhong; Li, Fu; Li, Zhongxiang; Liu, Hongxiu
Abstract : The rapid popularity of mobile shopping makes people's lives more convenient, but it also makes it easier for customers to change providers. How to use marketing stimulus to retain customers has become an urgent concern for mobile sales companies. However, the theoretical researches in this field are not enough. For this reason, this study used the methods of literature review and structural equation to explore the effects of mobile marketing design factors on the continual intention of consumers in mobile shopping by using the S-O-R model and its extended theories. The conclusions of the research showed that interface quality of mobile sales terminal and integrity of mobile sales terminal had significant positive impacts on consumption emotion; sales promotion in mobile sales terminal had a significant positive impacts on continual intention of mobile shopping; consumption emotion had a significant positive effect on continual intention of consumers in mobile shopping; consumption emotion played a significant mediating role in the relationship between interface quality of mobile sales terminal and continual intention of mobile shopping and between integrity of mobile sales terminal and continual intention of mobile shopping. The conclusions could not only enrich the theories of mobile shopping behavior but also provide guidance for companies to carry out mobile marketing activities and allocate marketing resources rationally.